Effectiveness of Problem Based Learning Model with Google Classroom Assistance on Learning Outcomes (Journal of Economic Education, 2022)
Learning in the current globalization period makes the government ready to implement a new curriculum update, namely the independent curriculum to encourage students to have the ability to solve problems. Problems based on data review in the field show that students are less accustomed to analyzing problems in economic lessons. Teachers need to innovate in the application of learning models and media. This study aims to analyze the effectiveness of Problem-based learning with google classroom to improve the economic learning outcomes of students in class XI IPS at SMA Negeri 107 Jakarta. This research uses a quantitative approach with a quasi-experimental design. The results of hypothesis testing show a significance value of 0.000 <0.05, tcount (7.268) > t table (1.99444) and the experimental class n-gain test of 0.41978 is higher than the control class of 0.223826. The conclusion of this study is that the problem-based learning model through google classroom is effective for improving the economic learning outcomes of class XI IPS at SMA Negeri 107 Jakarta.